THE URBANIZATION OF RURAL COMMUNITIES, BETWEEN THE SOCIAL NEED AND THE URBAN CULTURE INVASION - Mirela Cristiana NILĂ STRATONE (Challenges of the Knowledge Society)
In studying the relationship between urban and rural, it is necessary to address the needs of rural communities through the invasion of technological and informational progress. Urban rural migration and vice versa determined the translation movement of the traditions of rural communities that he moved to the city. From here, to the village, technology, information, urban values, both negative and positive, have begun. The existing differences tend to fade away. This is, on the one hand, a positive outcome in terms of improving the living conditions in the countryside, educational level and entertainment. On the other hand, we can also talk about a negative result, as the blurring of urban-rural boundaries leads, among other things, to the elimination and sometimes to the loss, of elements of tradition and folklore. An extremely important role, of course, is the family, as the nucleus of each community. Of course, it is not to be neglected its particularities, which outline the difference between the village family and the town family. However, even at the level of the family group we can see cultural changes. This group is opening up more and more, so gradually there can be noticed a diminishing of the differences between the rural family group and the urban family group. The constant migration of family members, from city to village and from village to city, leads to the intermingling of cultural values, a certain uniformization of education, a new family matrix in the future, valid for the entire population of the country. However, the differences will coexist with a certain form of uniformity. Alongside the vision of village development, it is also interesting to apply the urban culture at the village, the cultivation of traditional family values, as well as the tendency to eliminate the differences between village and city, both in terms of human lifestyle, comfort , and education.